Erotetic Language Style of Sūnwùkōng in the Drama Series Xīyóujì by Zhāngjìzhōng - Arista, Cicik; Subandi, Subandi; Mintowati, Mintowati; Hu, Yifan (English Lecturers and Teachers Association (ELTA), 2025)
Humans need language as a communication tool to send messages directly or indirectly. One way to communicate through indirect messages is by literature arts, such as drama series that can strengthen the impression of conveying the meaning of utterance. In this research, the use of erotetic language style by Sūnwùkōng in the drama series xīyóujì. This research aims to describe the forms and functions of erotetic language style by Sūnwùkōng. The erotetic language style is commonly used in speech or poetry, but in this drama series, Sūnwùkōng uses this style extensively in his utterance, therefore, this type of research is qualitative research because the data is based on the form of utterance of Sūnwùkōng, therefore the method used is a descriptive method. From the results of the analysis, 40 data were obtained with five kinds of stylistic markers of erotetic, including 5 data markers 难道 nándào; 12 marker data 怎么 zěnme; 4 marker data 这么 zhème; 8 marker data 呢 ne; and 11 吗 ma marker data. The function of erotetic language style expressed is as a form of emphasis on something, specifically angry, accusation, rejection, joy, surprise, amazed, and underestimate. Keywords : erotetic; language style; drama series; Sūn Wùkōng